Identifikasi Senyawa dari Ekstrak Air Rimpang Bangle (Zingiber cassumunar Roxb.) - SRI HARTATI; MEGAWATI MEGAWATI; NINA ARTANTI; MEILYAWATI L.; M. HANAFI (JURNAL ILMU KEFARMASIAN INDONESIA, 2013)
In a preliminary study on search of marker compounds from raw material phytopharmaceutical water extracts of medicinal herbs bangle (Zingiber casumunar Roxb.) three compounds, namely (E)-4-(3’,4’-dimethoxyphenyl)but-3-en-1-yl acetate (1), (E)-4(3’,4’-dimethoxyphenyl) but-3-en-1-1-ol (2) and 2-Methoxy-8-(3,4-dimethoxyphenyl)-1,4-napthoquinone (3) had been found. The isolation was done by partition and combination of chromatography techniques. The isolated pure compound was analyzed by spectroscopy methods of NMR proton and carbon one and two-dimensional, LC-MS and IR-spectrophotometry IR